Comparison of the efficacy of COVID-19 responses in South Korea and the United States - Oliver Choi; Sunjoo Kim (Global Health Action)
Background The COVID-19 pandemic devastated many countries worldwide by causing large numbers of fatalities. In our research, we wanted to answer the question: Why was there such a large difference in the mortality rate between South Korea and the United States? This is because many East Asian countries, such as Korea, had a lower mortality rate than many countries, including developed ones, across the world – the mortality rate of South Korea was about five times lower than the United States. Methods This study comprehensively compares strategies used to address the COVID-19 pandemic in two different countries: South Korea and the United States. The various aspects of these two countries’ responses are examined, including initial response, information dissemination and public compliance, mitigation strategies, and vaccine rollout and their impacts. Results Early and widespread testing, rigorous contact tracing, the clear release of government information, and an organized vaccine rollout powered a proactive approach in South Korea. The United States had a contrasting response consisting of delayed and more decentralized measures, where testing lagged due to varying policies and the political controversies facing vaccine distribution. Conclusions We signify the gravity of rapid response and testing, clear communication, and efficient vaccine distribution, as we believe this could correlate with a lower mortality rate. In addition, we discuss future directions, including the need for a specific health infrastructure and protocol against highly infectious outbreaks.